An Update on African Trypanocide Pharmaceutics and Resistance. - Keneth Iceland, Kasozi; MacLeod, Ewan Thomas; Ntulume, Ibrahim; Welburn, Susan Christina (Kabale University, 2023)
African trypanosomiasis is associated with Trypanosoma evansi, T. vivax, T. congolense, and T. brucei pathogens in African animal trypanosomiasis (AAT) while T. b gambiense and T. b rhodesiense are responsible for chronic and acute human African trypanosomiasis (HAT), respectively. Suramin sodium suppresses ATP generation during the glycolytic pathway and is ineffective against T. vivax and T. congolense infections. Resistance to suramin is associated with pathogen altered transport proteins. Melarsoprol binds irreversibly with pyruvate kinase protein sulfhydryl groups and neutralizes enzymes which interrupts the trypanosome ATP generation. Melarsoprol resistance is associated with the adenine-adenosine transporter, P2, due to point mutations within this transporter. Eﬂornithine is used in combination with nifurtimox. Resistance to eﬂornithine is caused by the deletion or mutation of TbAAT6 gene which encodes the transmembrane amino acid transporter that delivers eﬂornithine into the cell, thus loss of transporter protein results in eﬂornithine resistance. Nifurtimox alone is regarded as a poor trypanocide, however, it is effective in melarsoprol-resistant gHAT patients. Resistance is associated with loss of a single copy of the genes encoding for nitroreductase enzymes. Fexinidazole is recommended for ﬁrst-stage and non-severe second-stage illnesses in gHAT and resistance is associated with trypanosome bacterial nitroreductases which reduce fexinidazole. In AAT, quinapyramine sulfate interferes with DNA synthesis and suppression of cytoplasmic ribosomal activity in the mitochondria. Quinapyramine sulfate resistance is due to variations in the potential of the parasite’s mitochondrial membrane. Pentamidines create cross-links between two adenines at 4–5 pairs apart in adenine-thymine-rich portions of Trypanosoma DNA. It also suppresses type II topoisomerase in the mitochondria of Trypanosoma parasites. Pentamidine resistance is due to loss of mitochondria transport proteins P2 and HAPT1. Diamidines are most effective against Trypanosome brucei group and act via the P2/TbAT1 transporters. Diminazene aceturate resistance is due to mutations that alter the activity of P2, TeDR40 (T. b. evansi). Isometamidium chloride is primarily employed in the early stages of trypanosomiasis and resistance is associated with diminazene resistance. Phenanthridine (homidium bromide, also known as ethidium bromide) acts by a breakdown of the kinetoplast network and homidium resistance is comparable to isometamidium. In humans, the development of resistance and adverse side effects against monotherapies has led to the adoption of nifurtimox-eﬂornithine combination therapy. Current efforts to develop new prodrug combinations of nifurtimox and eﬂornithine and nitroimidazole fexinidazole as well as benzoxaborole SCYX-7158 (AN5568) for HAT are in progress while little comparable progress has been done for the development of novel therapies to address trypanocide resistance in AAT. Keywords:Trypanocides, Trypanosoma, Trypanosomiasis, Drug Resistance, HAT, AAT.